High-sensitive detection and quantitation of thyroid-stimulating hormone (TSH) from capillary/fingerstick and venepuncture whole-blood using fluorescence-based rapid lateral flow immunoassay (LFIA) - Samar Shurbaji (9938696) (2023)
Background In the last decade, point of care testing (POCT) such as lateral flow immunoassays (LFIA) were developed for rapid TSH measurement. Most of these TSH-LFIAs are designed for qualitative measurements (i.e., if TSH values > 5, or >15 IU/L) and as screening tests for primary hypothyroidism in children and adults. Serum or plasma, but not venepuncture whole-blood or fingerstick/capillary, are usually used to quantify TSH accurately. Studies on performance evaluation of TSH-LFIAs POCT using venepuncture or fingerstick whole-blood are limited. Additionally, limited studies evaluated the performance and validity of TSH-LFIAs POCT compared to valid and reliable reference methods. To our knowledge, this is the first study to evaluate three different blood withdrawal techniques for evaluating POCT of TSH. Aim We aim to evaluate the performance of a new fluorescence-based LFIA and its Finecare™ fluorescent reader for quantitative measurement of TSH from a fingerstick, venepuncture whole-blood, and serum. Methods 102 fingerstick, venepuncture whole-blood, and serum samples (with normal and abnormal TSH values) were analyzed by Finecare™ Rapid Quantitative LFIA test and Roche cobas® e 601 as a reference test. Results Using serum, when compared to cobas® e 601 reference method, Finecare™ showed high sensitivity [90.5 % (69.6–98.8)] and specificity [96.3 % (89.6–99.2)] for diagnosis of thyroid abnormalities (<0.35 or >4.5 mIU/L). The actual test values (mIU/L) of Finecare™ showed excellent agreement (Cohen's Kappa = 0.85) and strong correlation (r = 0.93, p < 0.0001) with cobas® e 601. Using venepuncture whole-blood samples, Finecare™ showed similar results to serum with high sensitivity [95.2 % (76.2–99.9)], specificity [97.5 % (91.4–99.7)], excellent agreement (Cohen's Kappa = 0.91), and very strong correlation (r = 0.95, p < 0.0001) with cobas® e 601. These results suggest that Finecare™ can be used for quantitative measurement of TSH using serum or venepuncture whole-blood. These key performance indicators were slightly decreased when fingerstick whole-blood samples were used: sensitivity [85.7 %(63.7–97)], specificity [90.0 %,(81.5–96)], good agreement (Cohen's Kappa = 0.7) and very strong correlation (r = 0.9, p < 0.0001) with cobas® e 601. A subgroup analysis of abnormal TSH samples revealed a strong and significant correlation between the reference, Finecare™ whole-blood (r = 0.692; p = 0.0015), and fingerstick test Finecare™ (r = 0.66; p = 0.0025). A very strong correlation was also observed between cobas® e 601 serum and Finecare™ serum (r = 0.88; p < 0.0001). Conclusion: In comparison to the reference assay, our study demonstrates that Finecare™ exhibits high sensitivity, specificity, agreement, and a strong correlation. These findings provide evidence that Finecare™ is a reliable, valid, and accurate point-of-care test for TSH screening and quantitative measurement, especially in non- or small laboratory settings. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2023.e20589